The Graptophyllum pictum extract effect on acrylic resin complete denture plaque growth - Endang Wahyuningtyas (Dental Journal (Majalah Kedokteran Gigi), 2005)
Graptophyllum pictum, in Indonesian is named ‘daun ungu’, is one of the traditional plants usually used as haemorrhoids medicament in Indonesia; it is composed from alkaloid, pectin, saponin, tannin, flavonoid and alcohol. Graptophyllum pictum is able to prevent the growth of Streptococcus mutans. The purpose of this investigation is to study the effect of Graptophyllum pictum extract toward the growth of plaque on acrylic resin complete denture. For this plaque growth research, 40 samples of acrylic resin complete denture were used, which divided into four groups. Those samples were first treated by cleansing each denture from saliva with running water. The existence of plaque on the complete denture was known by means of disclosing agent. The plaque was then scored by using modified Quigley Hein index, in this case until the plaque was scored zero. The second treatment was soaking the Group I to IV denture samples in Graptophyllum pictum extract with various concentration 5%, 10%, 20% and 40%, each for 15 minutes. Following this, the dentures were worn by the patients again for four hours, and then removed and washed with water. Then the disclosing agent were rubbed on the dentures and subsequently washed with water. The obtained data were analyzed by One-way variant analysis and t-test. The study result showed there were significant differences among the growth of plaque on acrylic resin complete denture which was soaked in different concentration of Graptophyllum pictum extract (p < 0.05). Regarding this result it can be concluded that Graptophyllum pictum extract could inhibit the plaque growth on acrylic resin complete denture. And it seems also that the highest plaque growth inhibition on acrylic resin complete denture is caused by the 40% concentration extract of Graptophyllum pictum.